Waiting Time and Patient Satisfaction in Mobile JKN Cardiology Services: Waktu Tunggu dan Kepuasan Pasien pada Layanan Mobile JKN Kardiologi - Yuniati, Rina; Fahrudda, Ansarul; Suswojo, Heru; Sari, Firdaus Indah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital health applications such as Mobile JKN are introduced to improve healthcare service efficiency, particularly in outpatient settings. Specific Background: Despite high utilization, outpatient waiting times at Mohammad Noer Regional General Hospital remain above the national standard, indicating persistent service delays. Knowledge Gap: Limited studies integrate actual waiting time (AWT) and perceived waiting time (PWT) in explaining patient satisfaction within digital health systems. Aims: This study examines the relationship between AWT, PWT, and patient satisfaction among Mobile JKN users in a cardiology clinic. Results: The average AWT reached 88.5 minutes, exceeding the national standard, with physician consultation as the main bottleneck. PWT showed a significant relationship with patient satisfaction (p < 0.05) and explained 44.5% of its variance. Both AWT and PWT significantly contributed to patient satisfaction, with perception playing a stronger role than objective duration. Novelty: This study integrates operational and experiential dimensions of waiting time within a digital health context, highlighting the dual role of objective and subjective measures. Implications: Improving patient satisfaction requires combining digital health systems with queue management, service optimization, and enhanced communication to align perceived and actual service performance. Highlights• Average service delay exceeds national outpatient standard duration• Perception of waiting explains substantial variation in satisfaction levels• Physician consultation identified as primary service bottleneck KeywordsActual Waiting Time; Mobile JKN; Perceived Waiting Time; Patient Satisfaction; Digital Health